Iron and mechanisms of neurotoxicity - Salvador, Gabriela Alejandra (2010)
The accumulation of transition metals (e.g., copper, zinc, and iron) and the dysregulation of their metabolism are a hallmark in the pathogenesis of several neurodegenerative diseases. This paper will be focused on the mechanism of neurotoxicity mediated by iron. This metal progressively accumulates in the brain both during normal aging and neurodegenerative processes. High iron concentrations in the brain have been consistently observed in Alzheimer's (AD) and Parkinson's (PD) diseases. In this connection, metalloneurobiology has become extremely important in establishing the role of iron in the onset and progression of neurodegenerative diseases. Neurons have developed several protective mechanisms against oxidative stress, among them, the activation of cellular signaling pathways. The final response will depend on the identity, intensity, and persistence of the oxidative insult. The characterization of the mechanisms mediating the effects of iron-induced increase in neuronal dysfunction and death is central to understanding the pathology of a number of neurodegenerative disorders.